Prospective assessment of tizanidine for spasticity due to acquired brain injury - Meythaler, Jay M.; Guin-Renfroe, Sharon; Johnson, Alice; Brunner, Robert M. (Archives of physical medicine and rehabilitation, 2001)
Meythaler JM, Guin-Renfroe S, Johnson A, Brunner RM. Prospective assessment of tizanidine for spasticity due to acquired brain injury. Arch Phys Med Rehabil 2001;82:1155-63. Objective: To determine if orally delivered tizanidine will control spastic hypertonia due to acquired brain injury. Design: Randomized, double-blind, placebo-controlled, crossover design, with 2 8-week treatment arms separated by a 1-week washout period at baseline. Patients were randomly assigned to receive tizanidine or a matching placebo. Setting: Tertiary care outpatient and inpatient rehabilitation center attached to a university hospital. Participants: Seventeen persons recruited in a consecutive manner, 9 of whom had suffered a stroke and 8 a traumatic brain injury, and had more than 6 months of intractable spastic hypertonia. Intervention: Over a 6-week period, subjects were slowly titrated up to their maximum tolerated dose (up to 36mg/d). Following a 1-week drug taper and 1-week period in which no study drug was administered, patients were then crossed over to the other study medication following an identical titration regime. Main Outcome Measures: Subjects were evaluated for dose and effect throughout the trial as well as for side effects. Data for Ashworth rigidity scores, spasm scores, deep tendon reflex scores, and motor strength were collected on the affected upper extremity (UE) and lower extremity (LE). Differences over time were assessed via descriptive statistics, Friedman's analysis, and Wilcoxon's signed-rank. Data are reported as the mean ± 1 standard deviation. Results: Following 4 weeks of treatment when subjects reached their maximal tolerated dosage, the average LE Ashworth score on the affected side decreased from 2.3 ± 1.4 to 1.7 ± 1.1 (p < .0001). The spasm score decreased from 1.0 ± 0.9 to 0.5 ± 0.8 (p = .0464), while the reflex score was not statistically significant decreasing from 2.2 ± 1.0 to 2.0 ± 1.1 (p = .0883). The average UE Ashworth score on the affected side decreased from 1.9 ± 1.1 to 1.5 ± 0.9 (p < .0001). There was no significant change in the UE spasm and reflex scores. While there were positive placebo effects on motor tone, the active drug was still significantly better than placebo for decreasing LE tone (p = .0006) and UE tone (p = .0007). With a reduction in motor tone, there was an increase in motor strength (p = .0089). The average dosage at 4 weeks was 25.2mg/d. Conclusion: Tizanidine is effective in decreasing the spastic hypertonia associated with acquired brain injury, which is dose-dependent. There are limitations on its use due to side effects related to drowsiness. © 2001 by the American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation